2010
DOI: 10.1021/jm9019068
|View full text |Cite
|
Sign up to set email alerts
|

“Carba”-Analogues of Fentanyl are Opioid Receptor Agonists‡ Dedicated to the memory of Ralph F. Hirschmann.

Abstract: There is evidence to indicate that the Asp residue in the third transmembrane helix (TMH) of opioid receptors forms a salt bridge with the positively charged nitrogen of endogenous and exogenous opioid ligands. To further examine the role of this electrostatic interaction in receptor binding and activation, we synthesized ‘carba’-analogues of a published fentanyl analogue containing a 3-(guanidinomethyl)-benzyl group in place of the phenyl moiety attached to the ethylamido group (C. Dardonville et al., Bioorg.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…This observation brought to another study, synthesis and investigation of its ‘carba’ -analogs. Compound devoid nitrogen atom in piperidine ring of fentanyl was synthesized and showed 25-fold reduced receptor binding affinities as compared with piperidine nitrogen containing but, surprisingly it retained its opioid agonist activity [167]. Moreover, in the same paper it was shown that the propionbenzylamino fentanyl analog has not only high μ-opioid binding (K i = 0.448 nM), but also had high κ receptor binding affinity (K i = 0.536 nM) (Supplementary Information 20).…”
Section: Replacement Of Anilino- Moiety For Benzylamino Groupmentioning
confidence: 99%
“…This observation brought to another study, synthesis and investigation of its ‘carba’ -analogs. Compound devoid nitrogen atom in piperidine ring of fentanyl was synthesized and showed 25-fold reduced receptor binding affinities as compared with piperidine nitrogen containing but, surprisingly it retained its opioid agonist activity [167]. Moreover, in the same paper it was shown that the propionbenzylamino fentanyl analog has not only high μ-opioid binding (K i = 0.448 nM), but also had high κ receptor binding affinity (K i = 0.536 nM) (Supplementary Information 20).…”
Section: Replacement Of Anilino- Moiety For Benzylamino Groupmentioning
confidence: 99%
“…[8] The very few compounds made without this pharmacophore [9] which retain agonist behavior are shown, consecutively numbered by the year of publication: the MOR-selective bicyclic enkephalin mimetic 2, [10] the k-opioid receptor (KOR)-selective neoclerodane diterpene salvinorin A (3), [11] the MORactive cyclic analogue of EM1 c[Tyr-d-Pro-d-Trp-Phe-Gly] (4), [12] and the "carba" analogues (both cis and the trans isomers) of a fentanyl equipped with a guanidino group (compound 5), in which the piperidine ring nitrogen atom is replaced by carbon. [13] Compound 5 likely retains the same binding mode as the "normal" fentanyls; however, it was observed that the 14) and to the cyclote-ionic bridge between the guanidine moiety of the ligands and an Asp in the second extracellular loop (EL) is significant for receptor binding. In contrast, compounds 3 and 4, which are deprived of any ionic interactions, have receptor binding modes different from that of the classical agonists.…”
Section: Introductionmentioning
confidence: 99%
“…Phenylethylcyclohexanone 4 was prepared as described. 11 An anhydrous modification of the Strecker reaction using 4 , aniline and trimethylsilyl cyanide (TMSCN) in glacial acetic acid 13 yielded isomers 5a and 5b (isomer ratio 1:3) in 90% yield. The conversion of nitriles 5a and 5b to amides 6a and 6b was performed with basic H 2 O 2 in DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…In a fentanyl analogue containing a 3-(guanidinomethyl)-benzyl group in place of the phenyl moiety attached to the ethylamide group, the piperidine nitrogen was replaced with a carbon ( 2 ). 11 The resulting cis and trans isomers ( 2a , 2b ) showed deceased MOR binding affinities but retained full MOR agonist activity, indicating that an electrostatic interaction of the protonated nitrogen in the piperidine ring of fentanil analogues with the THM3 Asp 147 residue is not a requirement for receptor activation. However, these ‘carba’-analogues still carry a positive charge on the guanidine group which, according to a performed receptor docking study, interacts with Asp 216 of the MOR.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation